Insecticidal Effects of Plasma Treated Water - ten Bosch, Lars (Int J Environ Res Public Health, 2017)
The efficacy of plasma-treated tap water (PTW) for the possible treatment of a mealybug (Planococcus citri) infestation was studied under laboratory conditions. Mealybugs growing on Nerium oleander have been treated using PTW after being transferred to Petri dishes, thus avoiding possible buffering effects that might occur in an in-situ study. When treating tap water with a dielectric barrier discharge for several minutes (1, 3, 5 and 10 min) a distinct acidification of the water can be determined, resulting in a pH value of 1.8 after 10 min treatment. The efficacies of the treated tap water samples were compared to the efficacies achieved using classically acidified water. The classical acidification of tap water was carried out using nitric acid and hydrochloric acid to see any possible influences of the salt of the acid in question. The application of PTW revealed high mortality rates of approx. 90% after an observation period of 24 h. PTW appears promising for the treatment of smaller plant stock and commodities as produced by small scale farmers or in greenhouses as an environmentally friendly substitute or supplement to conventional pesticides.